2019
DOI: 10.1007/s12182-019-00389-x
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary characteristics and internal architecture of a river-dominated delta controlled by autogenic process: implications from a flume tank experiment

Abstract: Autogenic processes are widely found in various sedimentary systems and they play an important role in the depositional evolution and corresponding sedimentary architecture. However, autogenic processes are often affected by changing allogenic factors and are difficult to be identified and analyzed from modern and ancient records. Through the flume tank experiment under constant boundary conditions, the depositional process, evolution principles, and the sedimentary architecture of a river-dominated delta was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…In this work, we provide evidence that an allogenic sea level forcing influences both surface processes and subsurface form. This finding is consistent with prior studies on the subject, which showed that steady SLR (e.g., Feng et al., 2019; Finotello et al., 2019; Guerit et al., 2021; Liang, Van Dyk, & Passalacqua, 2016; Martin, Sheets, et al., 2009) and base level cycles (e.g., Hajek et al., 2014; Kim et al., 2006; Koss et al., 1994; van Heijst & Postmal, 2001) impact both surface processes and the resulting stratigraphy. Uniquely, here, we focus on SLR acceleration by testing the impact that different future sea level trajectories may have on deltaic landscapes.…”
Section: Discussionsupporting
confidence: 93%
“…In this work, we provide evidence that an allogenic sea level forcing influences both surface processes and subsurface form. This finding is consistent with prior studies on the subject, which showed that steady SLR (e.g., Feng et al., 2019; Finotello et al., 2019; Guerit et al., 2021; Liang, Van Dyk, & Passalacqua, 2016; Martin, Sheets, et al., 2009) and base level cycles (e.g., Hajek et al., 2014; Kim et al., 2006; Koss et al., 1994; van Heijst & Postmal, 2001) impact both surface processes and the resulting stratigraphy. Uniquely, here, we focus on SLR acceleration by testing the impact that different future sea level trajectories may have on deltaic landscapes.…”
Section: Discussionsupporting
confidence: 93%
“…However, unsteady production of sediment in the source (Bull, 1991; Schumer et al., 2011; Sharman et al., 2019; Smith, 1994; Tucker & Slingerland, 1997), the climatic modulation of base level in the sink (Vail et al., 1977), and variable coupling between tectonics and surface processes that exhibit a range of autogenic behaviours (Beaumont et al., 1992; Hoffman & Grotzinger, 1993; Koons, 1989; Zeitler et al., 2001) obscure the record of tectonic forcing in sediments and sedimentary rocks (Romans et al., 2015; Straub et al., 2009). For example, surface autogenic processes (Feng et al., 2019; Foreman & Straub, 2017), effective diffusivity (Paola et al., 1993), characteristic time scales (Jerolmack & Sadler, 2007) and response times of the system ( τ ) (Whipple & Tucker, 1999) introduce significant uncertainty in how tectonic processes drive unsteady sediment yield (Jerolmack & Paola, 2010), how they can be interpreted from the architecture of sedimentary basin fill (Allen, 2008), or how they are used to infer the time preserved by sedimentary facies (Paola et al., 2018). Understanding how all of these factors operating on an erosional landscape, ultimately becoming the sedimentary facies in sedimentary basins, is crucial to inversion of the stratigraphic record (Sharman et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The marl is impermeable and the accumulation of rainwater and groundwater causes it to loosen. In this case, its upper layers become unstable and are driven by gravity or seismic force (12,13) .…”
Section: Main Features Of Marlsmentioning
confidence: 99%
“…To test, a sample of soil paste is placed in the cup and made by a groove in the middle of the groove dough. The groove on the bottom of the cup (13 cm long) is noted and then the amount of moisture in the soil is determined (12) , (13) ; To determine the amount of dough, the test soil is mixed with some distilled water and made into a paste. Then a portion of the sample (approximately 2.5 grams) is woven with fingers on a polished plate to a diameter of 6 mm and then tried to reduce its diameter to 3 mm.…”
Section: Atterberg Limitsmentioning
confidence: 99%